High Temperature Mid‐IR Polarizer via Natural In‐Plane Hyperbolic Van der Waals Crystals. Issue 4 (6th December 2021) - Sahoo, Nihar Ranjan; Dixit, Saurabh; Singh, Anuj Kumar; Nam, Sang Hoon; Fang, Nicholas X.; Kumar, Anshuman
Abstract: Integration of conventional mid to long‐wavelength infrared (IR) polarizers with chip‐scale platforms is restricted by their bulky size and complex fabrication. Van der Waals materials based polarizer can address these challenges due to its nonlithographic fabrication, ease of integration with chip‐scale platforms, and room temperature operation. In the present work, mid‐IR optical response of the sub‐wavelength thin films of α‐phase molybdenum trioxide (α‐MoO3 ) is investigated for application toward high temperature mid‐IR transmission and reflection type thin film polarizer. To the authors' knowledge, this is the first report of above room temperature mid‐IR optical response of α‐MoO3 to determine the thermal stability of the proposed device. It is found that the α‐MoO3 based polarizer retains high extinction ratio with peak value exceeding 10 dB, up to a temperature of 140 °C. The experimental findings are explained by natural in‐plane hyperbolic anisotropy of α‐MoO3 in the mid‐IR, high temperature X‐ray diffraction and Raman spectroscopic measurements. This work opens up new avenues for naturally in‐plane hyperbolic van der Waals thin‐films to realize sub‐wavelength IR optical components without lithographic constraints. Abstract : Mid and far‐infrared region of the electromagnetic spectrum is critical for thermal imaging, biosensing, and security, yet optical components in this range are not well developed. For the first time, a high temperature, lithography free mid‐infrared polarizer based on the natural biaxial hyperbolic van der Waals crystal α‐MoO3 with robust performance over a broad operational bandwidth is demonstrated.